EMPIRICAL RESEARCH ON ONLINE REPURCHASE INTENTION: AN ASSESSMENT OF EASE OF USE, SECURITY, PRIVATE CONCERN, TRUST, AND E-SATISFACTION TOWARDS ONLINE SHOPPERS IN CHINA - Wang, Renyan; Chaipoopirutana, Sirion (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Nowadays, e-commerce is more and more popular, and has become an indispensable part of people’s daily life. With the fantastic growth of online shopping quantity of Chinese users, the e-commerce platform is also overgrowing. This study focuses on five factors (security, ease of use, privacy concern, trust and e- satisfaction) that affect repurchase intention. In addition, this study focuses on China’s online shopping platform and online shopping users. This study collected 389 questionnaires by online platform and the data from the questionnaires were analyzed and summarized. Descriptive and inferential analyses were applied to analyze the data, and the researchers applied five point Likert scales for the research instrument. In this study, the researchers applied Simple Linear Regression and Multiple Linear Regression to test all the hypotheses. The results of this study show that “security” and “privacy concern” have great influence on trust and e-satisfaction. The website ease of use has an important impact on customers’ e-satisfaction. At the same time, the online security, e-satisfaction and trust have an important impact on customer repurchase intention.